Strategi Marketing Pendidikan di Pondok Pesantren Darul Muta’allimin Tanah Merah Aceh Singkil - Nur Helmi; Amiruddin Siahaan; Yusuf Hadijaya (Dinasti Review, 2024)
Islamic boarding schools have a very important role in efforts to provide education for the Indonesian people, especially in religious education. The era of globalization has had many impacts in various fields, one of which is the education sector, where competition between educational institutions has become more competitive. Islamic boarding schools are required to be able to promote their existence as educational institutions by implementing appropriate marketing strategies to maintain their existence and to attract public interest in the Islamic boarding school itself . The Darul Muta'allimin Islamic Boarding School is one of the oldest Islamic boarding schools in the Aceh Singkil region, which was founded in 1962 AD. However, this does not reduce the public's interest and trust in the Darul Muta'allimin Islamic Boarding School as a place to study. Based on initial observations made by researchers, the educational marketing strategy at the Darul Muta'allimin Islamic Boarding School is still less than optimal, carried out in an organized and planned way to be disseminated widely on social media to attract public interest. However, every year a large number of students still register. Based on this description, researchers are interested in conducting research related to educational marketing strategies carried out at the Darul Muta'allimin Tanah Merah Aceh Singkil Islamic Boarding School. The aim of this research is to analyze the educational marketing strategy at Darul Muta'allimin Islamic Boarding School, the marketing mix carried out at Darul Muta'allimin Islamic Boarding School, the obstacles faced in carrying out educational marketing mix and ways to overcome educational marketing mix obstacles at Darul Muta'allimin Islamic Boarding School. This research uses a research methodology using descriptive qualitative methods. The results of this research explain that the educational marketing strategy carried out at the Darul Muta'allimin Islamic Boarding School is carried out by carrying out promotions, creating routine activities, adjusting educational programs, highlighting their advantages, attractive financing strategies, and students and female students participating in community activities.